Descrição do potencial de retenção de nitrogênio em frangas de postura por diferentes metodologias: mínima retenção - Silva, Edney Pereira Da [UNESP]; Sakomura, Nilva Kazue [UNESP]; Bonato, Melina Aparecida [UNESP]; Donato, Daniella Carolina Zanardo [UNESP]; Peruzzi, Nelson José [UNESP]; Fernandes, João Batista Kochenborger [UNESP] (Universidade Federal de Santa Maria, 2014)
The objectives of this study were to describe the potential for nitrogen retention by two techniques: comparative slaughter and nitrogen balance; compare the adjusted models for each technique and estimate the maintenance requirement for pullets. Assays were performed during 14 to 28, 56-70 and 98 to 112 days of age, using 168 pullets. The design was completely randomized with seven treatments and eight replications. Treatments consisted of protein levels ranging from 75 to 435gkg-1 of dry matter. The variables were collected by comparative slaughter and nitrogen ingested and deposited in nitrogen balance technique intake and nitrogen excretion. The intercept of the exponential relationship between ingested and excreted nitrogen was considered a requirement for maintenance. The adjusted models were compared by using the maximum likelihood ratio. The techniques described differently compared the requirement for maintenance of nitrogen. For comparative slaughter requiring maintenance was estimated at 342, 372 and 543mg/kgPC0,67 and for nitrogen balance was 342, 225 and 284mg/kgPC0,67 for the period of 14 to 28, 56-70 and 98 to 112 days of age, respectively.

Objetivou-se com esta pesquisa descrever o potencial de retenção de nitrogênio por duas técnicas: abate comparativo e balanço de nitrogênio. Também se objetivou comparar os modelos ajustados para cada técnica e estimar as exigências de mantença para frangas de postura. Os ensaios foram realizados no período de 14 a 28, 56 a 70 e 98 a 112 dias de idade, utilizando 168 frangas. Os ensaios tiveram sete tratamentos e oito repetições. Os tratamentos consistiram de níveis de proteína variando de 75 a 435gkg-1 de matéria seca. As variáveis coletadas pelo abate comparativo foram nitrogênio ingerido e depositado e, pela técnica do balanço de nitrogênio, ingestão e excreção de nitrogênio. O intercepto da relação exponencial entre nitrogênio excretado e ingerido foi considerado a exigência de mantença. Os modelos ajustados foram comparados pelo teste da razão de máxima verossimilhança. As técnicas comparadas descreveram de forma diferente a exigência de mantença de nitrogênio. Para o abate comparativo, a exigência de mantença foi estimada em 342, 372 e 543mg/kgPC0,67 e para o balanço de nitrogênio foi de 342, 225 e 284mg/kgPC0,67, para os período de 14 a 28, 56 a 70 e 98 a 112 dias de idade, respectivamente.
Description of the potential for nitrogen retention in pullets by different methodologies: minimum retention
Keywords: exigência de mantença; balanço de nitrogênio; abate comparativo; requirement for maintenance; nitrogen balance; comparative slaughter